Evidence for negative thermal expansion in the superconducting precursor phase SmFeAsO. (12th February 2018) - Zhou, H D; Sarte, P M; Conner, B S; Balicas, L; Wiebe, C R; Chen, X H; Wu, T; Wu, G; Liu, R H; Chen, H; Fang, D F
Abstract: The fluorine-doped rare-earth iron oxypnictide series SmFeAsO1− x F x (0 ⩽ x ⩽ 0.10) was investigated with high resolution powder x-ray scattering. In agreement with previous studies (Margadonna et al 2009 Phys. Rev . B.79 014503), the parent compound SmFeAsO exhibits a tetragonal-to-orthorhombic structural distortion at T S   =  130 K which is rapidly suppressed by x ≃ 0.10 deep within the superconducting dome. The change in unit cell symmetry is followed by a previously unreported magnetoelastic distortion at 120 K. The temperature dependence of the thermal expansion coefficient α V reveals a rich phase diagram for SmFeAsO: (i) a global minimum at 125 K corresponds to the opening of a spin-density wave instability as measured by pump-probe femtosecond spectroscopy (Mertelj et al 2010 Phys. Rev . B81 224504) whilst (ii) a global maximum at 110 K corresponds to magnetic ordering of the Sm and Fe sublattices as measured by magnetic x-ray scattering (Nandi et al 2011 Phys. Rev . B84 055419). At much lower temperatures than T N, SmFeAsO exhibits a significant negative thermal expansion on the order of  −40 ppm · K −1 in contrast to the behaviour of other rare-earth oxypnictides such as PrFeAsO (Kimber et al 2008 Phys. Rev . B78 140503) and the actinide oxypnictide NpFeAsO (Klimczuk et al 2012 Phys. Rev . B85 174506) where the onset of α V < 0 only appears in the vicinity of magnetic ordering. Correlating this feature with the temperature and doping dependence of the resistivity and the unit cell parameters, we interpret the negative thermal expansion as being indicative of the possible condensation of itinerant electrons accompanying the opening of a SDW gap, consistent with transport measurements (Tropeano et al 2009 Supercond. Sci. Technol .22 034004).